Current Cesarean Section Rate and Factors Affecting the Patient Decision Regarding Mode of Delivery - Qadeer, Robina; Tehniyat Attiya ur Razaq; Humaira Khattak; Humaira Aman; Afrah Aman; Shamim Akthar (Journal of Postgraduate Medical Institute, 2024)
Objectives: To determine the current cesarean section rate and factors leading to Cesarean Section on Maternal Request (CSMR). Methodology: This is a descriptive cross-sectional study, conducted at the Obstetrics & Gynecology Unit of Kuwait Teaching Hospital in Peshawar. Data regarding cesarean section and factors affecting patient decisions regarding mode of delivery were collected through structured questionnaires from patients who provided informed consent. The study included patients admitted for a normal vaginal delivery but who requested to have optedhave an elective cesarean section, at.. Patients with obstetric indications for a C-section were excluded from the study. Data analysis was conducted using SPSS version 25 to determine percentages and frequencies. Results: The C-section rate was found to be 36.7%, with 10% of these cases being performed as Cesarean Section at Maternal Request (CSMR). Among the women, 154 (40.84%) had previously had a C-section and to undergo another elective C-section instead of attempting a trial of labor. Additionally, 76 (20.15%) of women declined admission. In 50 (13.26%) of cases, C-sections were performed based on the gender of the newborn, with a preference for male babies. Thirty-six (9.54%) of women had no living children from prior pregnancies. Other reasons for CSMR were conceiving after more than 5 years (7.95%), previous bad experience with vaginal delivery (5.30%), and going for tubal ligation (2.91%). Besides the above-mentioned factors, 26% of women were influenced by the opinions of close relatives and friends. Thirty-seven (10%) of women were encouraged by their doctors, while 3% chose to have a “C-Section on Maternal Request (CSMR)" along with a bilateral tubal ligation to complete their families. Conclusion: CSMR (Caesarean Section on Maternal Request) contributes significantly to the overall C-section rate. By addressing the factors influencing these decisions, the C-section rate could potentially be reduced.